Muscle MRI in patients with dysferlinopathy: pattern recognition and implications for clinical trials. Issue 10 (7th May 2018) - Diaz-Manera, Jordi; Fernandez-Torron, Roberto; LLauger, Jaume; James, Meredith K; Mayhew, Anna; Smith, Fiona E; Moore, Ursula R; Blamire, Andrew M; Carlier, Pierre G; Rufibach, Laura; Mittal, Plavi; Eagle, Michelle; et al.
Abstract : Background and objective: Dysferlinopathies are a group of muscle disorders caused by mutations in the DYSF gene. Previous muscle imaging studies describe a selective pattern of muscle involvement in smaller patient cohorts, but a large imaging study across the entire spectrum of the dysferlinopathies had not been performed and previous imaging findings were not correlated with functional tests. Methods: We present cross-sectional T1-weighted muscle MRI data from 182 patients with genetically confirmed dysferlinopathies. We have analysed the pattern of muscles involved in the disease using hierarchical analysis and presented it as heatmaps. Results of the MRI scans have been correlated with relevant functional tests for each region of the body analysed. Results: In 181 of the 182 patients scanned, we observed muscle pathology on T1-weighted images, with the gastrocnemius medialis and the soleus being the most commonly affected muscles. A similar pattern of involvement was identified in most patients regardless of their clinical presentation. Increased muscle pathology on MRI correlated positively with disease duration and functional impairment. Conclusions: The information generated by this study is of high diagnostic value and important for clinical trial development. We have been able to describe a pattern that can be considered as characteristic of dysferlinopathy. We have defined the natural history of the disease from a radiological point of view. These results enabled the identification of the most relevant regions of interest for quantitative MRI in longitudinal studies, such as clinical trials. Clinical trial registration: NCT01676077 .